Factores de riesgo que influyen en el desarrollo de enfermedades diarreicas agudas en niños menores de 5 años que asisten al Centro de Salud Nuevo San Juan, periodo junio-octubre 2023. - Chimborazo Sangacha, Johana Jessenia (2023)
Acute diarrheal diseases are infections of the digestive tract caused by bacteria, viruses or parasites, whose main symptom is diarrhea, affecting 25% of all children in Ecuador, causing death due to dehydration. Objective: Determine the risk factors that influence the development of acute diarrheal diseases in children under 5 years of age who attend the Nuevo San Juan Health Center, period June-October 2023. Methodology: The research design was non-experimental, modality quantitative, descriptive, field and transversal. A survey was used to collect data. Results: In sociodemographic factors, 20 to 29 years old (48.8%), female sex (81.4%), primary educational level (46.5%), civil union status (55.8%) and rural residence (91.9%), in the environmental, dirt floor (36%), 1 room (41.9%), electric energy service (40.7%), boiled water for human consumption (66.3%) and overcrowding (57%), and in personal matters, sometimes hand hygiene prior to food preparation (53.5%), storage of food in the environment (65.1%), without protection of garbage (59.3%). and cats inside the home (41.9%); the frequency of acute diarrhea was 67.4%; and lack of knowledge of parents about the disease and dehydration. Conclusion: There are various sociodemographic, cultural and personal factors associated with the development of acute diarrhea in children, which is why it is necessary to strengthen health education in the community.